Liberia : Poverty Reduction Strategy Paper: Annual Progress Report. (IMF Staff Country Reports; Country Report, 2012)
This report assesses the design, implementation, and effectiveness of Liberia's first Poverty Reduction Strategy (PRS). The PRS described the objectives for each pillar and sector, often with numerical projections, and these were essentially the intended outcomes. The Economic Corridors study and anecdotal evidence suggest that the initial emphasis on providing inputs to stimulate production brought farmers up against constraints in storage, transport and marketing, leading them to pull back on production after they encountered difficulty in selling their produce.